2018
DOI: 10.1080/15205436.2018.1442479
|View full text |Cite
|
Sign up to set email alerts
|

Back to Reality: The Complex Relationship Between Patterns in Immigration News Coverage and Real-World Developments in Dutch and Flemish Newspapers (1999–2015)

Abstract: Although prior studies investigating immigration news typically documented a dominant focus on negativity and threats, only limited empirical research is available, which scrutinizes the way real-world developments affect these patterns in immigration news. This study aims to fill this void. First, we report results of a large-scale and longitudinal content analysis (N = 4,340,757) of trends in immigration news coverage in two Western European cases, Flanders (the northern, Dutch-speaking, largest region of Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…In fact, German immigration news coverage had a distinct peak in late 2001, right after 9/11 (Boomgaarden & Vliegenthart, 2009). Jacobs, Damstra, Boukes, and De Swert (2018), however, found that the relationship between immigration media coverage and real world developments (e.g. immigration or crime statistics) is low overall.…”
Section: Media Salience Of Issues and Actorsmentioning
confidence: 99%
“…In fact, German immigration news coverage had a distinct peak in late 2001, right after 9/11 (Boomgaarden & Vliegenthart, 2009). Jacobs, Damstra, Boukes, and De Swert (2018), however, found that the relationship between immigration media coverage and real world developments (e.g. immigration or crime statistics) is low overall.…”
Section: Media Salience Of Issues and Actorsmentioning
confidence: 99%
“…In the context of political communication, studies have documented the discrepancies between media coverage and real-world developments (e.g. Jacobs et al 2017;Vliegenthart and Boomgaarden 2007) and the over-time tendency of media to become increasingly focused on negative incidents (e.g. Farnsworth and Robert Lichter 2006;Semetko and Schoenbach 2003).…”
Section: Disproportional Attention To Negative Newsmentioning
confidence: 99%
“…In other words, does the volume of media reports on negative or riskrelated incidents increase over time while real-world data show a decreasing trend of these incidents and how do these patterns relate to public responses? By exploring the relation between patterns in news attention and trends of real-world events, this research touches upon the journalistic core principle of news production (Jacobs et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations